Assessing the appropriateness of helicopter emergency medical services for non-traumatic emergencies in a medically underserved rural area, Japan - Shohei Matsubara; Ken-ei Sada; Masataka Kudo; Sho Sasaki; Atsushi Morizane; Koshi Kajihara; Hidenao Okubo; Kosuke Hamagawa; Toshimi Mizobuchi; Toshikazu Yabe; Yuichi Saisaka; Kimiaki Tanaka; et al. (PLoS ONE, 2026)
Background Helicopter emergency medical services (HEMS) are essential in trauma care, but their role in non-traumatic emergencies remains unclear, particularly in medically underserved rural areas where long total prehospital times and limited specialty care access complicate emergency response. Objectives To evaluate the appropriateness of HEMS dispatches in non-trauma emergencies by assessing undertriage and overtriage based on clinical necessity and total prehospital time in rural western Kochi Prefecture, Japan. Methods We conducted a retrospective cohort study of adult patients (≥18 years) requiring emergency transport for moderate to severe non-traumatic conditions during HEMS operational hours from 2017 to 2021. HEMS necessity was classified as “absolute” (treatment unavailable at local core hospitals) or “relative” (critical condition benefiting from shorter transport). Appropriateness was defined as concordance between actual transport modality and predefined necessity criteria, with undertriage and overtriage determined by comparing the actual primary HEMS dispatch requests against these criteria and regional total prehospital times. Results Of the 2,312 eligible patients, 63 received primary HEMS dispatches and 2,249 ground EMS (GEMS). Among HEMS dispatches, 56 of 63 (88.9%) were overtriaged, while seven (11.1%) were appropriately triaged. Among GEMS transports, 248 of 2,249 (11.0%) retrospectively met HEMS criteria, yielding an 11.0% undertriage rate. Overtriaged cases included patients lacking relative necessity criteria or total prehospital time advantage. Conclusions In medically underserved rural regions, clinical severity alone may be insufficient for determining HEMS necessity in non-traumatic emergencies. Incorporating total prehospital time advantage and regional infrastructure consideration may refine dispatch decision-making and improve HEMS utilization appropriateness.